Time Course of Changes in Peripheral Blood Gene Expression During Medication Treatment for Major Depressive Disorder - Cook, Ian A.; Congdon, Eliza; Krantz, David E.; Hunter, Aimee M.; Coppola, Giovanni; Hamilton, Steven P.; Leuchter, Andrew F. (Frontiers in Genetics, 2019)
Changes in gene expression (GE) during antidepressant treatment may increase understanding of the action of antidepressant medications and serve as biomarkers of efficacy. GE changes in peripheral blood are desirable because they can be assessed easily on multiple occasions during treatment.  We report here on GE changes in 68 individuals who were treated for eight weeks with either escitalopram alone, or escitalopram followed by bupropion.  GE changes were assessed after one, two, and eight weeks of treatment, with significant changes observed in 156, 121 and 585 peripheral blood gene transcripts, respectively.  Thirty-one transcript changes were shared between the one- and eight-week time points (seven upregulated, 24 downregulated).  Differences were detected between the escitalopram- and bupropion-treated subjects, although there was no significant association between GE changes and clinical outcome.  A subset of 18 genes overlapped with those previously identified as differentially expressed in subjects with MDD compared with healthy control subjects.  There was statistically significant overlap between genes differentially expressed in the current and previous studies, with 10 genes overlapping in at least two previous studies.  There was no enrichment for genes overexpressed in nervous system cell types, but there was a trend toward enrichment for genes in the WNT/β-catenin pathway in the anterior thalamus; three genes in this pathway showed differential expression in the present and in three previous studies.  Our dataset and other similar studies will provide an important source of information about potential biomarkers of recovery and for potential dysregulation of GE in MDD.